Analysis of job burnout in people working in sports in the universities of Baghdad - Ali Jamel Nasser; Qutaiba Hussein Alwan; Mohannad Salman Dawood (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.